2016
DOI: 10.4314/tjpr.v15i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Antilipolytic and hypotriglyceridemic effects of dietary <i>Salvia triloba</i> Lf (Lamiaceae) in experimental rats

Abstract: Purpose: Pancreatic triacylglycerol lipase (PL) is a noteworthy pharmacological target for the management of dyslipidemia, and diabetes and obesity. This study was aimed to evaluate the modulatory effects of Salvia triloba L.f. (Lamiaceae) leaves methanol extract (ME) on a high fat diet (HFD)-induced hypertriglyceridemia in rats, with complementary in vitro evaluation of sage PL-inhibitory potential. Methods: Pre-induction of HFD hypertriglyceridemia sage leaves ME (750 mg/kg) was orally supplemented (via gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…This could possibly be owed to its main phenolic component, i.e., luteolin-7- O -glucoside, since its aglycone has been reported to be a good lipase inhibitor [52,53], a hypothesis also supported by the high correlation found between the content of this flavone and the anti-lipase activity (0.930, data not shown). Interestingly, the anti-lipase activity of polar extracts of Salvia species has been previously described, namely for the methanolic extract of the leaves of S. officinalis (EC 50 = 94 μg/mL) [54], the methanol extract of Salvia spinosa (EC 50 = 156.2 μg/mL) [55], and methanol extracts of Salvia triloba (EC 50 = 100.8 μg/mL) [56]. Hence, despite data from literature that seems to suggest that at least some polar extracts from Salvia species might be promising with respect to their abilities to control the activity of α-amylase and pancreatic lipase, this was not the observed for S. officinalis, S. elegans and S. greggii decoctions herein studied.…”
Section: Resultsmentioning
confidence: 99%
“…This could possibly be owed to its main phenolic component, i.e., luteolin-7- O -glucoside, since its aglycone has been reported to be a good lipase inhibitor [52,53], a hypothesis also supported by the high correlation found between the content of this flavone and the anti-lipase activity (0.930, data not shown). Interestingly, the anti-lipase activity of polar extracts of Salvia species has been previously described, namely for the methanolic extract of the leaves of S. officinalis (EC 50 = 94 μg/mL) [54], the methanol extract of Salvia spinosa (EC 50 = 156.2 μg/mL) [55], and methanol extracts of Salvia triloba (EC 50 = 100.8 μg/mL) [56]. Hence, despite data from literature that seems to suggest that at least some polar extracts from Salvia species might be promising with respect to their abilities to control the activity of α-amylase and pancreatic lipase, this was not the observed for S. officinalis, S. elegans and S. greggii decoctions herein studied.…”
Section: Resultsmentioning
confidence: 99%
“…Although less investigated, the ability of polar Salvia extracts to inhibit lipase was previously reported. In particular, methanolic extracts obtained from S. officinalis leaves [91] and from S. triloba [92], and dichloromethane extracts of other sage species, were previously reported to hold this ability [87]. In the study of Ninomiya et al [91], the authors also emphasized the ability of the phenolic diterpenes carnosic acid and carnosol, isolated from leaves of S. officinalis, to control the activity of pancreatic lipase [91].…”
Section: Antidiabetic and Anti-obesity Properties Of Salvia Extracts-in Vitro Methodsmentioning
confidence: 98%
“…In vivo models also support the hypothesis that Salvia phenolic-rich extracts have anti-obesity and antidiabetic properties (Table 4). Among them, it was demonstrated that treatment via gastric intubation of high fat diet rats with methanolic extracts of S. triloba (750 mg/kg body wt) [92], or the dietary supplementation of olive oil-loaded mice with a methanolic extract of S. officinalis leaves (doses of 500 and 1000 mg/kg) for 14 days [91], suppressed serum triglyceride increases. Notably, in this latter study, the authors also attested that carnosic acid (10 mg/kg) significantly inhibited triglyceride elevation in olive oil-loaded mice [91].…”
Section: Antidiabetic and Anti-obesity Properties Of Salvia Extracts-in Vitro Methodsmentioning
confidence: 99%
“…Diğer bir çalışmada ise Salvia fruticosa metanol ekstraktının, sıçanlarda lipid sindirimi ve emiliminde rol oynayan önemli gastrointestinal enzimleri inhibe edebildiği, bu nedenle adaçayının obezite ile ilişkili hipertrigliseridemiyi kontrol etmek için potansiyel bir fitoterapötik/profilaktik strateji olabileceği sonucuna varılmıştır. Ayrıca adaçayının, vücut kilo alımını bastırmak için potansiyel olarak kullanılabileceğini gösteren çift hipotrigliseridemik ve antilipolitik özelliklere sahip olduğu belirtilmiştir [96]. Bu çalışmalara ek olarak, Salvia fruticosa yapraklarının metanol ekstresinin, streptozotosin/nikotinamid ile oluşturulan diyabetik sıçan modelinde hiperglisemi düzeylerini düşürdüğü, glikoz toleransını arttırdığı ve diyabetik sıçanlarda hiperinsülinemiyi önlediği bildirilmiştir [97].…”
Section: Anti-hiperglisemik Etkiunclassified